The use of abrasive wastes in the practice of wastewater treatment from nickel ions - Porozhnyuk, L; Lupandina, N; Porozhnyuk, E (International Journal of Engineering and Technology, 2018)
The results of sewage treatment from nickel ions are given in the article. The relevance of the studies is determined by the expansion of the spectrum of effective sorbents-reagents as a result of the use of industrial wastes. Mineralogical and component compositions of abrasive waste are studied. The process of sorption and desorption of nickel ions on the wastewas studied by theconstruction isotherm method and a mixed character of sorption processes with a predominance of physical interactions was established.Â Â